2013
DOI: 10.1128/aem.02378-13
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Quorum-Quenching Compounds

Abstract: c Bacteria have the remarkable ability to communicate as a group in what has become known as quorum sensing (QS), and this trait has been associated with important bacterial phenotypes, such as virulence and biofilm formation. Bacteria also have an incredible ability to evolve resistance to all known antimicrobials. Hence, although inhibition of QS has been hailed as a means to reduce virulence in a manner that is impervious to bacterial resistance mechanisms, this approach is unlikely to be a panacea. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 57 publications
2
69
0
Order By: Relevance
“…Through the adenosine screening, C-30-resistant mutants were identified that have mutations in the mexR and nalC genes. Both genes encode transcriptional repressors of the mexAB-OmpR operon, which encodes a multidrug resistance efflux pump that we showed is able to efflux C-30 when its expression is de-repressed (Maeda et al, 2012;García-Contreras et al, 2013a).…”
Section: Qs Enhances the Oxidative Stress Response Through The Producmentioning
confidence: 99%
“…Through the adenosine screening, C-30-resistant mutants were identified that have mutations in the mexR and nalC genes. Both genes encode transcriptional repressors of the mexAB-OmpR operon, which encodes a multidrug resistance efflux pump that we showed is able to efflux C-30 when its expression is de-repressed (Maeda et al, 2012;García-Contreras et al, 2013a).…”
Section: Qs Enhances the Oxidative Stress Response Through The Producmentioning
confidence: 99%
“…Although they observed "resistance", they did not validated their data experimentally. However, simultaneously, a group provided evidence that resistance to QQ is indeed possible (Maeda et al 2012;García-Contreras et al 2013). Anand et al (2013) used an experimentally validated computational model of LuxI/LuxR QS to study the effects of using inhibitors individually and in combination.…”
Section: Quorum Quenchingmentioning
confidence: 99%
“…One attractive feature of such therapies is that it was hypothesized that unlike growth inhibition-based therapies, anti-virulence therapies should be impervious to resistance (Rasmussen and Givskov, 2006;Bjarnsholt et al, 2010;Rasko and Sperandio, 2010). However, recently it was demonstrated that the generation and selection of resistance against quorum quenchers (QQs) occurs as readily as it does for antibiotics, under conditions in which growth is directly coupled to QS (García-Contreras et al, 2013b;Kalia et al, 2013;Maeda et al, 2012). Experimentally, these conditions are achieved by growing the bacterial pathogen Pseudomonas aeruginosa with adenosine as sole carbon source, as its catabolism is tightly dependent on a functional LasR QS system (Heurlier et al, 2005) and as it is metabolized internally by the QS-proficient bacteria.…”
mentioning
confidence: 99%